1998
DOI: 10.1038/sj.jhh.1000512
|View full text |Cite
|
Sign up to set email alerts
|

Monogenic forms of mineralocorticoid hypertension: insights into the pathogenesis of ‘essential’ hypertension?

Abstract: Hypertension is a common condition, which, depending on its definition, affects 10-25% of the population. Because it is an established risk factor for coronary and cerebrovascular disease, hypertension has, quite rightly, been targeted as an important factor in determining the health of the nation. Despite this we can explain the underlying cause of a patient's hypertension in Ͻ5% of cases; the remainder are labelled 'essential' hypertension, an elegant way of stating that the aetiology is unknown. As a result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1998
1998
2001
2001

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 75 publications
0
4
0
Order By: Relevance
“…Whereas an argument exists for attempting complete suppression of abnormally regulated aldosterone production in patients with FH-I (see below), this approach would also be expected to render patients at significant risk of Cushingoid side effects. Indeed, occasional reports (21) of glucocorticoidinduced side effects in treated patients have caused some investigators to express caution in the use of glucocorticoids (22,23) and, in the case of affected children, to favor the use of other agents (such as amiloride) to avoid the growthretarding effects of glucocorticoid treatment in this age group (24). In the current study of eight patients with genetically proven FH-I, glucocorticoid doses of 0.125-0.25 mg dexamethasone daily or 2.5-5 mg prednisolone daily were sufficient to maintain normal blood pressure throughout 0.5-3.8 yr of follow-up without the need for additional antihypertensive medication.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas an argument exists for attempting complete suppression of abnormally regulated aldosterone production in patients with FH-I (see below), this approach would also be expected to render patients at significant risk of Cushingoid side effects. Indeed, occasional reports (21) of glucocorticoidinduced side effects in treated patients have caused some investigators to express caution in the use of glucocorticoids (22,23) and, in the case of affected children, to favor the use of other agents (such as amiloride) to avoid the growthretarding effects of glucocorticoid treatment in this age group (24). In the current study of eight patients with genetically proven FH-I, glucocorticoid doses of 0.125-0.25 mg dexamethasone daily or 2.5-5 mg prednisolone daily were sufficient to maintain normal blood pressure throughout 0.5-3.8 yr of follow-up without the need for additional antihypertensive medication.…”
Section: Discussionmentioning
confidence: 99%
“…79 The potential importance of abnormal renal tubular sodium reabsorption as a determinant of sodium balance and of blood pressure has been highlighted by genetic studies of renal sodium transporters in rare familial conditions. 80 For example, Liddle's syndrome is a rare autosomal dominant disorder caused by a molecular defect leading to increased activity of the renal epithelial sodium channel. The increased renal sodium reabsorption and sodium retention leads to high blood pressure and suppression of plasma renin activity.…”
Section: Renal Epithelial Sodium Channelmentioning
confidence: 99%
“…1 Until recently, however, there were no clues to the molecular basis of GS, another variety of salt-sensitive familial hypertension. Important progress was made in the recent study by Mansfield et al, 6 in which evidence for linkage to chromosomes 1 and 17 was found.…”
Section: Discussionmentioning
confidence: 99%